Extraction of caffeine from spent coffee using aqueous solutions of ionic liquids - Gomes, Hugo André do Monte (2015)
The main objective of this work consists on the development of a more benign and efficient technique for the extraction of added-value compounds from biomass. In particular, the use of ionic liquids (ILs) for the extraction of caffeine from spent coffee was investigated. This compound display important properties with relevance in food, pharmaceutical, cosmetic and agrochemical industries. Spent coffee grounds (SCG) are a waste product without commercial value, being thus a raw material with virtually no cost and with a huge potential of value-added compounds able to be extracted. To this end, solid-liquid extractions from biomass were carried out using aqueous solutions of various ILs as well as mixtures of ILs and salts. As a first attempt, several protic Ils (PILs) were synthesized and characterized. These were chosen since they have unique characteristics that facilitate their recovery as well as the separation of the extracted components. The results obtained indicate that triethanolammonium acetate is the best candidate to extract caffeine. More specifically, at the concentration of 2 M, a temperature of 358 K (85°C), a solid-liquid ratio of 0,1 and 45 minutes of extraction time, it was achieved a value of extracted caffeine of 3.01% (w/w). Aqueous solutions of different aprotic ILs, with a common cholinium cation, were also investigated for the extraction of caffeine. A factorial planning was carried out in order to identify the optimum operating conditions. The optimum operating conditions for caffeine extraction with aqueous solutions of cholinium bicarbonate were obtained in the following conditions: time of 30 minutes, temperature of 323 K (50°C), solid-liquid ratio of 0.05 and LI concentration of 1.5 M, where the value of caffeine extraction obtained was of 1.85% (w/w). Mixtures of salts with hydrotropic characteristics with ILs were finally investigated for the extraction of caffeine in order to combine the properties of both classes of compounds. It has been found that the compounds containing the tosylate anion have a higher ability to extract caffeine. In addition, the LI 1-butyl-3-methylimidazolium tosylate or an equimolar mixture of sodium tosylate with 1-butyl-3-methylimidazolium chloride, lead to similar values of extracted caffeine. More specifically, for a concentration of 1M, the value obtained for the extraction of caffeine was of 3.50% (w/w), at a temperature of 348 K (75°C), extraction time of 30 minutes and solid-liquid ratio of 1:10. In summary, this thesis describes the application of aqueous solutions of ILs foreseeing the development of more efficient and sustainable extractive processes.